1974
DOI: 10.1021/i360050a011
|View full text |Cite
|
Sign up to set email alerts
|

Deposit Formation from Deoxygenated Hydrocarbons. I. General Features

Abstract: The study of the variables which control the rate of deposit formation from hydrocarbon jet fuels exposed to high-temperature stress is extended to the effect of the removal of dissolved molecular oxygen. Deposit formation rate measurements have been extended to higher temperatures (150-649°C) and pressures (18-69 atm) than previously employed In fuel stability studies. With most fuels, removal of molecular oxygen markedly lowered the rate of deposit formation. However, the poorest quality fuel tested did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 7 publications
2
34
0
Order By: Relevance
“…Previous research has shown that the formation of thermal deposits is greatly affected by the sulfur concentration of the fuel. [12][13][14] Other fuel characteristics, such as lubricity and storage stability, are also dramatically affected by the amount of sulfur in the fuel, in both positive and negative ways. 15 Simultaneous with jet engine development, the chemical composition of petroleum-derived jet fuels has been studied in an attempt to understand how the chemical composition of the fuel affects engine performance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that the formation of thermal deposits is greatly affected by the sulfur concentration of the fuel. [12][13][14] Other fuel characteristics, such as lubricity and storage stability, are also dramatically affected by the amount of sulfur in the fuel, in both positive and negative ways. 15 Simultaneous with jet engine development, the chemical composition of petroleum-derived jet fuels has been studied in an attempt to understand how the chemical composition of the fuel affects engine performance.…”
Section: Introductionmentioning
confidence: 99%
“…For fuel stressed at 430 K, as in the T = 380 K case, the absorption appears to be dominated by molecular absorption. These indicated changes in the fuel's molecular components are not surprising since other studies have shown that fuel deposition on heated surfaces is influenced by the system's chemistry Wallace, 1967, 1968;Taylor, 1969Taylor, , 1974Taylor, , 1976. This shift is indicative of changes in the molecular absorbers for the system.…”
Section: 8mentioning
confidence: 66%
“…1A. DF of 0.45 ml was manually loaded in a CO 2 environment to avoid the trapping of air because oxygen affects fuel stability [17,[22][23][24][25]. The oven temperature (T 1 ) and the fuel temperature (T 2 ) were measured by two thermocouples and recorded by a data acquisition system (LabVIEW, National Instruments).…”
Section: Batch Thermal Stressing Of Dfmentioning
confidence: 99%
“…In addition, it has been reported that thermal decomposition of liquid hydrocarbon fuels (jet fuel, DF, etc.) falls into three different regimes [15] Transition regime (300-500 o C): Both autoxidation and pyrolysis reactions contribute to decomposition and the rate of decomposition decreases with increase in fuel temperature possibly due to the transition from the liquid phase to the supercritical phase which enhanced solvent capability [17] or due to depletion of hydroperoxides [16].…”
Section: Introductionmentioning
confidence: 99%